(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
Distance education (EaD) takes advantage of technology, which leads to a discussion on the Massive Online Open Courses (MOOCs), their concept, features, and technological integration. The purpose of this paper was to analyze the concept of MOOC for their proper characterization through the literature review. The methodology was based on an integrative literature review with no cut-off date, in addition to the use of Boolean operators. A total of 37 documents were analyzed in which it was found that the concept, its characteristics, and degrees of technological integration are as broad as the educational needs to which they respond. It is concluded that the MOOCs are not entirely faithful to their acronym and that the high number of characteristics they possess makes it difficult for them to have a unique definition because they change and adapt quickly, in addition, it must be prudent to use them in higher education. Research into the teaching and learning skills required for MOOCs is recommended, along with the causes of high dropout rates.